2019
DOI: 10.18510/hssr.2019.7548
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Person-Organization Fit in the Relationship Between Socially Responsible-HRM Practices and Employee Engagement

Abstract: Purpose of study: This study investigates the relationship between employee engagement and Corporate Social Responsibility (CSR), which draws insights from social exchange theory. Specifically, it examines the effect of socially responsible human resource management practices (SR-HRM) on employee engagement. Methodology: The empirical work in the present study was conducted in Malaysia. The measurement instruments for Socially Responsible HRM Practices, P-O Fit, and employee engagement were adopted.  The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 64 publications
(75 reference statements)
2
7
0
Order By: Relevance
“…The fundamental basis of the research conducted in this article was formed by the Theory of Human Resource Management (HRM). According to this theory, humanization of entrepreneurship implies responsible management of human resources, which is manifested in the following: Preservation and creation of additional jobs to support employment and fight unemployment (Liao et al, 2022 ; Omidi and Dal Zotto, 2022 ); Optimization and organization of jobs through an increase in their comfort and safety (del-Castillo-Feito et al, 2022 ; He et al, 2021 ; Sorribes et al, 2021 ); Provision of opportunities for career building and development of human potential through the creation of knowledge-intensive jobs, with creative activities and innovative activity of employees (Diaz-Carrion et al, 2019 ; Latan et al, 2022 ; Rawshdeh et al, 2019 ; Zhang et al, 2015 ), as well as the creation of highly productive jobs, which imply the use of the leading technologies and automatization means, in particular, the support of decent jobs for digital personnel (Ramos-González et al, 2022 ). …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamental basis of the research conducted in this article was formed by the Theory of Human Resource Management (HRM). According to this theory, humanization of entrepreneurship implies responsible management of human resources, which is manifested in the following: Preservation and creation of additional jobs to support employment and fight unemployment (Liao et al, 2022 ; Omidi and Dal Zotto, 2022 ); Optimization and organization of jobs through an increase in their comfort and safety (del-Castillo-Feito et al, 2022 ; He et al, 2021 ; Sorribes et al, 2021 ); Provision of opportunities for career building and development of human potential through the creation of knowledge-intensive jobs, with creative activities and innovative activity of employees (Diaz-Carrion et al, 2019 ; Latan et al, 2022 ; Rawshdeh et al, 2019 ; Zhang et al, 2015 ), as well as the creation of highly productive jobs, which imply the use of the leading technologies and automatization means, in particular, the support of decent jobs for digital personnel (Ramos-González et al, 2022 ). …”
Section: Literature Reviewmentioning
confidence: 99%
“…• Provision of opportunities for career building and development of human potential through the creation of knowledge-intensive jobs, with creative activities and innovative activity of employees (Diaz-Carrion et al, 2019;Latan et al, 2022;Rawshdeh et al, 2019;Zhang et al, 2015), as well as the creation of highly productive jobs, which imply the use of the leading technologies and automatization means, in particular, the support of decent jobs for digital personnel (Ramos-González et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirical research showed the positive effect of employees’ perceptions of their organization’s socially responsible practices on their outcomes such as identification, loyalty, commitment, trust, and satisfaction ( Brammer et al, 2007 ; Rupp et al, 2013 ; Rawshdeh et al, 2019 ). Melynyte and Ruzevicius (2008) a survey that was conducted in 25 countries supported the idea that organizations’ engagement in social responsibility enhanced the employee’s motivation and loyalty.…”
Section: Hypotheses and Conceptual Frameworkmentioning
confidence: 99%
“…Although PO fit researchers have long been interested in the relationship of PO fit and its effects on employee perceptions or behaviours, it is only relatively recently that employee engagement (EE) has emerged as a focus for this work. Researchers (e.g., Chawla 2020;Hicklenton et al 2019;Kao et al 2021;Lv and Xu 2018;Memon et al 2018;Rawshdeh et al 2019;Sekhar et al 2018) have asked whether increasing employees' PO fit increases their EE, leading to stronger intentions to stay, more promotive voice behaviours, (i.e., making suggestions for issues that may improve the work unit), more internal and external organizational citizenship behav- iours (OCBs), perceived need satisfaction, and better job performance. Generally, the answers are yes, though the increase in EE varies.…”
Section: Contemporary Theme 1: Engagementmentioning
confidence: 99%
“…Kao et al (2021) found that PO fit strengthens the direct effect of EE on promotive voice behaviour (as well as the indirect effect of job autonomy on promotive voice behaviour through EE). PO fit has been found to partially mediate the positive relationship between employer branding and EE (Chawla 2020) and socially responsible HRM practices and EE (Rawshdeh et al 2019). Flexible HRM makes the employee more 'organization fit' and more engaged for their respective job, which in turn improves their job performance (Sekhar et al 2018).…”
Section: Contemporary Theme 1: Engagementmentioning
confidence: 99%